Evaluation of energy efficiency, visualized energy, and production of environmental pollutants of a solar flat plate collector containing hybrid nanofluid. (October 2022) - Mustafa, Jawed; Alqaed, Saeed; Sharifpur, Mohsen
Abstract: Energy efficiency, visualized energy, and production of environmental pollutants of a solar flat plate collector containing water/copper–aluminum hybrid nanofluid are evaluated. The results are compared with water/aluminum oxide nanofluid and water. The Reynolds number (Re) for the investigation is between 700 and 2300, and the nanoparticles volume fraction is 0.1%. A developed model in the engineering equations solver is used to solve the governing equations. The outputs show that the most suitable collector operating fluid is the hybrid nanofluid. Collector energy efficiency employing hybrid nanofluid is more than other operating fluids, and its maximum increment applying mono and hybrid nanofluids relative to water is 3.86 and 4.23 %, respectively. The criterion evaluation performance of the collector in the presence of hybrid nanofluid is larger than mono-nanofluid of aluminum oxide–water. Environmental analysis of the collector shows that the productions of sulfur oxides, carbon dioxide, and nitrogen oxides in a solar flat plate collector are maximum and minimum for water and hybrid nanofluid, respectively. In the case of hybrid nanofluid, the rate of production reduction of carbon dioxide, sulfur oxides and nitrogen oxides are respectively 29.15 kg, 0.0149 kg and 0.0255 kg compared to water. However, these amounts are 26.64 kg, 0.0136 kg and 0.0233 kg for mono nanofluids, respectively.